Correlation of Seblak Consumption to Hypertension in Generation Z: Korelasi Konsumsi Seblak Terhadap Hipertensi Pada Generasi Z - Setyawan, Yuswanto (Jurnal Ilmiah Kesehatan, 2025)
This research aims to find out how spicy eating (seblak) is related to hypertension in generation Z. The research method used was cross-sectional with a descriptive model analyzed using SPSS with the chi-square test and Spearman correlation test. The population is all generation Z who consume seblak in Sidoarjo Regency, a total sample of 100 consisting of 50 women and 50 men. The results of this research are that based on research and analysis carried out on generation Z consumption of seblak and hypertension, it was found that out of 100 people who consumed seblak, 50 men and 50 women related to the tendency to experience hypertension, women were accompanied by the most symptoms, namely dizziness with a percentage of 19-28% and on average generation Z did not know if they had hypertension, the most symptom was heart palpitations with a percentage of 23-28%. This research shows that consuming seblak can increase the risk of hypertension in generation Z, especially women. As a suggestion for further research, it is hoped that research will focus more on UPF foods or ultra-processed foods contained in spicy foods and their impact on generation Z.   Keywords: Spicy Food, Hypertension, Generation Z